Numerical simulations of laser-driven experiments of ion acceleration in stochastic magnetic fields - Moczulski, K; Wen, H; Campbell, T; Scopatz, A; Arrowsmith, C; Bott, A; Sarkar, S; Schekochihin, A; Gregori, G (American Institute of Physics, 2024)
We present numerical simulations used to interpret laser-driven plasma experiments at the GSI Helmholtz Centre for Heavy Ion Research. The mechanisms by which non-thermal particles are accelerated, in astrophysical environments e.g., the solar wind, supernova remnants, and gamma ray bursts, is a topic of intense study. When shocks are present the primary acceleration mechanism is believed to be first-order Fermi, which accelerates particles as they cross a shock. Second-order Fermi acceleration can also contribute, utilizing magnetic mirrors for particle energization. Despite this mechanism being less efficient, the ubiquity of magnetized turbulence in the universe necessitates its consideration. Another acceleration mechanism is the lower-hybrid drift instability, arising from gradients of both density and magnetic field, which produce lower-hybrid waves with an electric field which energizes particles as they cross these waves. With the combination of high-powered laser systems and particle accelerators it is possible to study the mechanisms behind cosmic-ray acceleration in the laboratory. In this work, we combine experimental results and high-fidelity threedimensional simulations to estimate the efficiency of ion acceleration in a weakly magnetized interaction region. We validate the FLASH MHD code with experimental results and use OSIRIS particle-in-cell (PIC) code to verify the initial formation of the interaction region, showing good agreement between codes and experimental results. We find that the plasma conditions in the experiment are conducive to the lower-hybrid drift instability, yielding an increase in energy ∆E of ∼ 264 keV for 242 MeV calcium ions.